Indonesian’s Industrial Decission on Self-Generated Electricity - Adi Setiya Grahito (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
This study analyzes the factors that determine firms' decisions on self-generated electricity in Indonesia. Specifically, I explore the difference in industries' decisions making across Indonesian five major islands in the past ten years. The empirical investigation utilizes Indonesian's Large and Medium Firm dataset of the years 2004, 2009, and 2014 from Indonesian Statistics. The empirical results show that an industry with higher output, higher income, and less labor is positively associated with the probability of having a self-generated electricity. Moreover, for firms that located in Kalimantan and Papua/Nusa Tenggara/Maluku island, they have a higher probability (24.7% and 19.8%, in comparison with Jawa/Bali island) of the self-generated electricity. The industry that plays in agriculture sector is also more likely to self-generate electricity. The year effect on the study indicates that in 2009 the industries reduce the usage of self-generated electricity. All of these findings are robust across different model specifications.